Osteomyelitis due to Mycobacterium haemophilum in an adult renal transplant recipient. (2023) - Chen, Benjamin; Mehta, Sanjay
Abstract: Mycobacterium haemophilum is an increasingly recognized pathogen of the non-tuberculous mycobacteria family that largely infects immunocompromised adults and immunocompetent children. M. haemophilum is a fastidious and slow-growing organism that exhibits preferential growth at lower temperature with iron supplemented media, and therefore most clinical manifestations involve cutaneous infection or musculoskeletal infection of the distal extremities. It is believed that opportunistic infection occurs in immunocompromised hosts when the organism is acquired through environmental exposure. We describe the case of a 71-year-old renal transplant recipient who developed acute M. haemophilum osteomyelitis of the left foot, likely contracted from Epsom salt soaks with contaminated tap water. Outcomes of M. haemophilum infection are generally favorable in the literature. Our patient was treated with local debridement and partial amputation followed by a 3-drug anti-mycobacterial regimen until definitive amputation could be completed.